Congenital Langerhans cell histiocytosis with hematological manifestations: a rare case - Mintoo, Sanjay Kumar; Kumar, Rajesh; Luthra, Jasbeer Kaur (International Journal of Contemporary Pediatrics, 2025)
Langerhans cell histiocytosis is a rare disorder of immune cells typically found in skin whose abnormal proliferation leads to inflammation and multi organ damage. It is even rarer in the neonatal population, particularly in preterm neonates. The clinical manifestations of disease could be limited or skin or involve multiple organs to become the more lethal multi systemic LCH. The risk organs include liver, spleen and bone marrow. Immuno histo chemistry using Langerin (CD207) and CD1a provide a definitive diagnosis. The case report is of a preterm neonate with Multisystemic involvement of skin, eyes and bone marrow and aims to highlight the importance of having a high degree of clinical 37 suspicion for early diagnosis and timely treatment of the disease. Despite modern advancements the prognosis for these patients remains bleak.